Thermo-electromagnetic effect on weld microstructure in magnetically assisted laser welding of austenite steel. (May 2019) - Chen, Xin; Luo, Manlelan; Hu, Renzhi; Li, Ruidi; Liang, Lvjie; Pang, Shengyong
Highlights: Applying a magnetic field of 415 mT doubled the width of the transition region. The TEC and TEMF can reach about 3.0 × 10 6 A/m 2 and 1.0 × 10 6 N/m 3 respectively. An intensive parameters R T i estimating TEMF on weld microstructure was proposed.. Abstract: Large microstructure gradients in high-power-density welding usually have negative effects on the mechanical properties of weld joints. In this paper, we found that the width of the weld microstructure in transition region was widened (from 65 μm to 140 μm) by applying a static axial magnetic field of 415 mT on the welding process, which efficiently improved the microstructure gradient. Based on our robust comprehensive model, we quantitatively predicted the distributions of thermoelectric currents (TEC) and thermo-electromagnetic force (TEMF) near the liquid-solid (L–S) interface. The three-dimensional annular TEC can reach about 3.0 × 10 6 A/m 2 near the L–S interface. The TEMF vertical to the L–S interface with applying a magnetic field of 415 mT on welding process can reach 1.0 × 10 6 N/m 3 or even larger, which could influence the fluid flow in weld pool and finally the weld microstructure. Furthermore, an intensive parameter of TEMF R T i (a dimensionless ratio) was proposed to estimate the effect of TEMF on the weld microstructure and the estimated results obtained good agreements with experimental data. Using this method, the critical value of the applied magnetic field which can cause the weld microstructure improvement in transition region obviously was predicted to be about 150 mT. Our findings and method can be served as guidance or reference for weld microstructure and joint quality optimization in laser welding process.